Immunization, sensibility, and the ressentiments of finance - Ute Tellmann (Finance and Society, 2021)
Vogl describes how digital economies and current financialization have a common genealogy that hinges on protocol and information. How should we understand the anatomy of power that governs this contemporary configuration? As argued in this review, the notion of 'immunity' can help illuminate the techniques of power at work in digital economies, social media, and finance.
Keywords: 300